Effect of anemia on the prognosis of patients with ventricular tachyarrhythmias - Weidner, Kathrin; Zworowsky, Max von; Schupp, Tobias; Hoppner, Jorge; Kittel, Maximilian; Rusnak, Jonas; Kim, Seung‑Hyun; Abumayyaleh, Mohammad S. A.; Borggrefe, Martin; Barth, Christian; Ellguth, Dominik; Taton, Gabriel; et al. (The American journal of cardiology, 2021)
This study evaluates the prognostic impact of anemia in patients presenting with ventricular tachyarrhythmias. The present longitudinal, observational, registry-based, monocentric cohort study included retrospectively all consecutive patients presenting with ventricular tachyarrhythmias on admission from 2002 to 2016. Anemic patients (hemoglobin levels <12.0 g/dl) were compared with non-anemic patients (hemoglobin levels ≥12.0 g/dl). The primary endpoint was all-cause mortality at 2.5 years. Secondary endpoints were cardiac death at 24 hours, all-cause mortality at index hospitalization, and the composite endpoint of cardiac death at 24 hours, recurrent ventricular tachyarrhythmias, and appropriate ICD therapies at 2.5 years. A total of 2,184 consecutive patients were included, of whom 30% were anemic and 70% non-anemic. Anemia was associated with the primary endpoint of all-cause mortality at 2.5 years (65% vs 29%, p = 0.001; HR = 2.441; 95% CI 2.086 to 2.856), cardiac death at 24 hours (26% vs 11%, p = 0.001), all-cause mortality at index hospitalization (45% vs 20%, p = 0.001), and the composite endpoint (35% vs 27%, p = 0.001; HR = 2.923; 95% CI 2.564 to 4.366). After multivariable adjustment, anemia was no longer associated with the composite endpoint. Predictors of adverse prognosis for anemics were CKD (HR = 2.191), LVEF <35% (HR = 1.651), cardiogenic shock (HR = 1.591), CPR (HR = 1.460), male gender (HR = 1.379), and age (HR = 1.017). In conclusion, anemic patients presenting with ventricular tachyarrhythmias were associated with increased long-term mortality at 2.5 years but not with the composite arrhythmic endpoint at 2.5 years. Predictors of adverse prognosis at 2.5 years were CKD, LVEF <35%, cardiogenic shock, CPR, male gender, and age.
Gesehen am 24.01.20023